Realita Sosial Dalam Naskah Drama Abad Tak Bermoral Karya Munief Doang - Suprapti Suprapti (STIKes Ibnu Sina Ajibarang, 2025)
Literary works are the result of thought, imagination, and reflection of the culture of a community group. Every society with a particular culture will produce literary works that contain depictions of human interactions with each other and their relationship with the surrounding environment. In this context, literary works not only serve as a form of aesthetic expression of the author regarding the reality he observes, but also become a means to convey life values. A good literary work is generally able to guide, educate, and provide enlightenment to its readers through the moral messages and truth values contained therein. In addition to its entertainment function, literary works also serve as a medium of social control conveyed in a fictional dimension. This is due to the fact that literary works are born from objective reality which is then processed through the author's imagination into a new reality full of meaning. In Indonesia, imaginative literary works are generally divided into three main forms, namely poetry, fiction or narrative prose, and drama. Drama, as a form of literary work, has its own uniqueness because it presents dialogue, plot, and characters directly, thus containing elements of beauty as well as implicit messages that are worthy of analysis. This research focuses on the analysis of the drama